2020
DOI: 10.7759/cureus.8088
|View full text |Cite
|
Sign up to set email alerts
|

Making the Cut: Implementing a Low Cost, Low Fidelity Simulation Model for Teaching Emergency Thoracotomy Procedure

Abstract: Emergent thoracotomy is a rare but high-stakes procedure for trauma patients. Emergency medicine residents are expected to perform this procedure after graduation, but few get the opportunity to perform it, leading to suboptimal performance and patient morbidity and mortality. Previous low-cost thoracotomy trainers revolve around modifying an existing costly thoracotomy task trainer or bear limited resemblance to actual landmarks and anatomy. This study attempts to bridge this gap by creating a low-cost model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…6,7 Additionally, CST is classified as a High Acuity Low Occurrence (HALO) procedure, meaning it is a ‘high-stakes’ procedure with very limited opportunities for observation or practice. 2,8,9…”
Section: Introduction and Objectivesmentioning
confidence: 99%
See 2 more Smart Citations
“…6,7 Additionally, CST is classified as a High Acuity Low Occurrence (HALO) procedure, meaning it is a ‘high-stakes’ procedure with very limited opportunities for observation or practice. 2,8,9…”
Section: Introduction and Objectivesmentioning
confidence: 99%
“…6,7 Additionally, CST is classified as a High Acuity Low Occurrence (HALO) procedure, meaning it is a 'high-stakes' procedure with very limited opportunities for observation or practice. 2,8,9 Given these factors, it is important to explore other avenues by which clinicians may become comfortable with CST. While options for simulation of CST do exist, commercially available models are expensive and this can inhibit widespread use.…”
Section: Introduction and Objectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Commercially available simulation training models for both procedures are often expensive and lack interactive elements. Low-cost simulators reported by other authors for ultrasound-guided pericardiocentesis and open thoracostomy have shown promising results, highlighting the value of low-cost simulators for teaching these high-acuity procedures [ 6 - 10 ]. Lord et al’s 3D-printed low-cost pericardiocentesis model was well-received by emergency medicine residents in the United States, with 92% of the residents “strongly agreeing” that the models effectively mimicked the clinical scenario [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In general, commercial medical training models are no option for CO 2 studies, because they are not designed to be gastight and are expensive. Thus, we took inspiration from some low-cost and "home-made" alternatives that have been developed, especially for student training in emergency thoracotomy [10][11][12]. We dedicated this technical report to give a detailed description of a thoracotomy model that is specifically designed for CO 2 field-flooding studies and can also be used for training other surgical procedures.…”
Section: Introductionmentioning
confidence: 99%